PROFITABILITY, CORPORATE GOVERNANCE, AND FAMILY OWNERSHIP EFFECT ON CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE - I Made Gde Kamal Mulia; Jati, I Ketut; Widhiyani, Ni Luh Sari; Sisdyani, Eka Ardhani (KRISNA: Kumpulan Riset Akuntansi, 2025)
The aim of this research is to analyze the effect of profitability, corporate governance, and family ownership on corporate social responsibility disclosure. This research was conducted on manufacturing sector companies listed on the Indonesia Stock Exchange with the observation year 2021 - 2023. The sample for this research is family companies (Family Business Enterprise) which are included in the manufacturing industry group. The sampling method used was the purposive sampling method. This research uses secondary data obtained from the official website of the Indonesia Stock Exchange, namely www.idx.co.id and the company's official website. The data collection method used in this research is the non-participant observation method. The data analysis technique used is multiple linear regression analysis. The findings show that profitability, corporate governance, and family ownership have a positive effect on corporate social responsibility disclosure.